Analisis Miskonsepsi Mahasiswa dengan Menggunakan Certainty of Response Index (CRI) Pada Materi Anatomi Tubuh Manusia - Kurniasih, Mike Dewi (IAIN Palangka Raya, 2017)
The aim of this research was to identify and analyse the studentâs misconception on human anatomy. This is a descriptive research with survey method. Instrument that is used are interview and misconception diagnostic test which include Certainty of Response Index (CRI) with range 0-5. This research identify that most of the studentâs misconception appears on topic excretory system anatomy with 42,22 % dan regulatory system anatomy with 40,00%. Generally the average of student misconception on human anatomy is 27,62 %. There are 3 items of diagnostic test that shows the highest misconception, they are blood vessels color, lungs size dan the function of urethra in male and female. Misconception that is identified are commonly about structure, location, color and the organ size. Based on the interview, the factors that built the studentâs are their prior concept. The prior concept formed since they were in elementary school until they became university student. Teacher, textbook, experience and learning method are contribute on their misconception.